Electrical characterization of metal-DNA-metal device under the influence of magnetic field / Nadia Mahmoudi Khatir - Mahmoudi Khatir, Nadia (2013)

(untitled)
Recently, Deoxyribonucleic Acid (DNA) has become an interesting candidate for conduction of electrical current. The outcome could be useful in nanotechnology and nanoelectronics for the design of electrical circuits, which could in turn help to overcome the limitations that classical silicon (Si)-based electronics would be facing in coming years. In this work, DNA strands from Bosenbergia rotunda were used as the fundamental element.The aim of this study was based on electrical characterization of gold (Au)-DNA-Au and Aluminium (Al)-DNA-Al structures under the presence and absence of external magnetic fields. The present work was investigated in two parts. First part involved using DNA as a material to create nano-gaps (NGs); DNA strands mixed in buffer solutions were applied onto thin films of Al on Si enabling chemical interactions between the strands and metal. This creates nanometer scale arbitrary patterning when directly transferring the DNA strands onto the Al substrate. This simple and costeffective method may in future be utilized in the fabrication of various components in electronic chips for Nanoelectromechanical (NEM) and Microelectromechanical (MEM) systems application in general.The second type of work utilized DNA as a semiconducting material in Metal-DNAMetal(MDM) structures. Au thin film evaporated using thermal evaporation technique was employed for fabricating the MDM structure (Au-DNA-Au structures). Its electrical behavior without and when subjected to an external magnetic field (up to 1200mT) was studied through its current-voltage (I-V) curves. Acquisition of the I-V curves demonstrated that DNA as a semiconductor exhibits diode behavior in the MDM structure. The current versus magnetic field strength followed a decreasing trend because of a diminished mobility in the presence of a low magnetic field. This made clear that an externally imposed magnetic field would boost resistance of the MDM structure up to 1000 mT. For higher magnetic field strengths, an increase in potential barrier was observed in the MDM junctions. The magnetic sensitivity achieved in this work indicates the promise of using MDM structures as potential magnetic sensors.